Inquiry-based Blended Learning Design for Physics Course: The Effectiveness and Students’ Satisfaction - Wayan Suana (Universitas Lambung Mangkurat, 2022)
This paper describes the effects of implementing inquiry-based blended learning (IBBL) design on students' learning achievement and satisfaction in an undergraduate physics course. This study employed the one group pre-test – post-test experiment design with a sample of 32 students who took an undergraduate level basic physics course. Learning design and devices applied in this research have been validated by three experts in physics education. 'Schoology', a virtual learning management system, was used as the online learning platform. One cycle of inquiry phases was conducted in the blended learning format of ‘pre-online–face to face–post-online learning’. The data were collected through tests, a scale, and a questionnaire. The test consisted of 35 multiple-choice questions with five alternative answers. It was designed to measure students’ abilities in remembering, understanding, applying, and analyzing. The satisfaction scale ranging from 1 (strongly disagree) to 5 (strongly agree) consisted of 21 items and covered the attractiveness, ease of use, and benefits of learning using the learning products. Furthermore, the questionnaire consisted of six open-ended questions asking about the obstacles and benefits students faced during the learning activities. The results showed that the students’ learning outcomes increased sufficiently. Besides, students’ satisfaction with the learning design and materials was also positive. These initial findings imply that inquiry-based learning (IBL) may be implemented in physics teaching using a blended learning format that can be more effective and efficient.